Characterisation of Colletotrichum Species Associated with Anthracnose of Banana - Latiffah Zakaria,; Shamsiah Sahak,; Maziah Zakaria,; Baharuddin Salleh, (Tropical Life Sciences Research, 2009)
A total of 13 Colletotrichum isolates were obtained from different banana cultivars (Musa spp.) with symptoms of anthracnose. Colletotrichum isolates from anthracnose of guava (Psidium guajava) and water apple (Syzygium aqueum) were also included in this study. Based on cultural and morphological characteristics, isolates from banana and guava were identified as Colletotrichum musae and from water apple as Colletotrichum gloeosporiodes. Isolates of C. musae from banana and guava had similar banding patterns in a randomly amplified polymorphic DNA (RAPD) analysis with four random primers, and they clustered together in a UPGMA analysis. C. gloeosporiodes from water apple was clustered in a separate cluster. Based on the present study, C. musae was frequently isolated from anthracnose of different banana cultivars and the RAPD banding patterns of C. musae isolates were highly similar but showed intraspecific variations. Sebanyak 13 pencilan Colletotrichum telah diperolehi daripada gejala antraknos pada kultivar pisang (Musa spp.) yang berbeza. Pencilan Colletotrichum daripada antraknos jambu batu (Psidium guajava) dan jambu air (Syzygium aqueum) turut disertakan dalam kajian ini. Berdasarkan ciri-ciri kultur and morfologi pencilan-pencilan Colletotrichum daripada pisang dan jambu batu, Colletotrichum musae telah dikenalpasti dan Colletotrichum gloeosporiodes pula dipencilkan daripada jambu air. Daripada analisis polimorfisma DNA rawak teramplifikasi (RAPD) menggunakan empat pencetus menunjukkan corak jalur C. musae daripada pisang dan jambu batu adalah serupa dan analisis kluster mengelompokkan pencilan-pencilan C. musae dalam kelompok yang sama. C. gloeosporiodes daripada jambu batu dikelompokkan dalam kluster yang berasingan. Berdasarkan kajian yang telah dijalankan, C. musae kerap dipencilkan daripada gejala antraknos kultivar pisang yang berlainan dan corak jalur RAPD pencilanpencilan C. musae adalah sangat serupa tetapi menunjukkan variasi intraspesifik.